Diastereoselective Photocycloaddition Reaction of Vinyl Ether Tethered to 1, 4‐Naphthoquinone. Issue 5 (14th March 2019) - Ishikawa, Hiroki; Chung, Tim S.; Fukuhara, Gaku; Shigemitsu, Hajime; Kida, Toshiyuki; Bach, Thorsten; Mori, Tadashi
Abstract: The intramolecular asymmetric photocycloaddition between 1, 4‐naphthoquinone and vinyl ether with a small ( R )‐point‐chiral group on the tether was studied. Under photoirradiation, [2+2] cyclobutane products were exclusively obtained for this intramolecular system. The effect of solvent polarity on the stereoselectivity was significant, with predominant formation of the (2 R, S 3 ) over the (2 R, R 3 ) isomer in non‐polar solvents being reversed in slightly polar dichloromethane. The detailed temperature‐dependent study revealed the dominant diastereo‐differentiating processes, which were switched between the ground‐state equilibrium, the relative rate of bond formation in the triplet manifold, as well as deactivation processes between the pro‐( S 3 ) and pro‐( R 3 ) precursors, depending on the temperature domain examined. The enthalpic contribution (ΔΔ H ≠ ) was always compensated by the entropic factor (ΔΔ S ≠ ), implying the importance of solvation on the diastereo‐differentiation steps. The mechanism of photocycloaddition, especially for the face‐selective processes, is thoroughly discussed, which is supported by quantum chemical calculations on the ground‐state circular dichroism (CD) spectral behavior as well as on the diastereomeric transition states in the triplet excited state. Abstract : Poles apart : In an intramolecular asymmetric photocycloaddition between 1, 4‐naphthoquinone and vinyl ether, the effect of solvent polarity on the diastereoselectivity was significant, with predominant formation of the (2 R, S 3 ) over the (2 R, R 3 ) isomer in non‐polar solvents being reversed in slightly polar dichloromethane. A detailed temperature‐dependent study revealed the dominant diastereo‐differentiating processes.